TETRAPOD FOOTPRINT ICHNO-ASSOCIATIONS FROM FRENCH PERMIAN BASINS. COMPARISONS WITH OTHER EURAMERICAN ICHNOFAUNAS - Gand G.E.; Durand M. (My University, 2006)
In order to take into account the studies of the European and American (USA) collections carried out by one of the authors, and of the recent nomenclatural revisions from new footprint discoveries, which have occurred during the last decade, the authors present a critical review of the French Permian palichnofauna. The distribution of the ichnospecies in the stratigraphy of the Lodève Basin, taken as a reference, is outlined. The ichno-associations are then compared with those of other French (Provence), European (Italy, Germany) and USA basins. Based on the ages of different ichnofossiliferous formations, three successive ichnofaunal units can be distinguished in the Permian of Europe. The first developed in the Cisuralian (Asselian to Kungurian). The second is found in the south of France in Kazanian to Lower Tatarian strata, equivalent to the Roadian-Wordian. The third and youngest, dated as Lopingian, is only found in Italy, in the Bolzano Basin. Because of sedimentary gaps, limited observations, sometimes erroneous determinations, and ichnospecies with great vertical distribution, it currently appears that footprints have a low utility for biochronological resolution. Nevertheless, they allow as to discriminate three time intervals in the Permian, as is also the case for skeletal remains. © The Geological Society of London.
Keywords: Lopingian; Cisuralian; Paleozoic::Permian::Lopingian; Палеозой::Пермская::Лопинский; Paleozoic::Permian::Cisuralian; Палеозой::Пермская::Приуральский